The distribution of Hibiscus L. section furcaria in tropical East Africa - Edmonds, J.M.; International Board for Plant Genetic Resources (1991)
This survey is to provide the necessary background data on which germplasm-collecting expeditions could be based, by identifying those species of potential use in the future genetic improvement of kenaf and rosella and by identifying those countries and locations where collecting expeditions would be most profitable.